Use Discriminant Analysis to Identify Eroticism-Related Terms in The Lyrics of Dangdut Songs - Herry Wahyu Wibowo; Muhammad Hasbi; Mochammad Anshori (Institut Teknologi, Sains, dan Kesehatan RS.DR. Soepraoen Kesdam V/BRW, 2024)
The song